2017
DOI: 10.3389/fnins.2017.00261
|View full text |Cite
|
Sign up to set email alerts
|

Phase-II Clinical Validation of a Powered Exoskeleton for the Treatment of Elbow Spasticity

Abstract: Introduction: Spasticity is a typical motor disorder in patients affected by stroke. Typically post-stroke rehabilitation consists of repetition of mobilization exercises on impaired limbs, aimed to reduce muscle hypertonia and mitigate spastic reflexes. It is currently strongly debated if the treatment's effectiveness improves with the timeliness of its adoption; in particular, starting intensive rehabilitation as close as possible to the stroke event may counteract the growth and postpone the onset of spasti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…In a later version, bio-inspired morphological characteristics were introduced by adding the compliance in the mechanical design using nonlinear elastic elements and custom-made torsional springs [97]. NEUROExos was developed by carefully analyzing the neuro-scientific motion requirement, and later, it was used in several experimental studies to cure neurological disorders [68].…”
Section: Neuroexosmentioning
confidence: 99%
“…In a later version, bio-inspired morphological characteristics were introduced by adding the compliance in the mechanical design using nonlinear elastic elements and custom-made torsional springs [97]. NEUROExos was developed by carefully analyzing the neuro-scientific motion requirement, and later, it was used in several experimental studies to cure neurological disorders [68].…”
Section: Neuroexosmentioning
confidence: 99%
“…In fact, the focus is to coordinate distal joints (the elbow and wrist) properly in order to proceed correctly toward the target (the mouth), also emphasizing the role of proprioceptive feedback in relation to the motor output. The main requirement of the task involves flexing the elbow against gravity, so spasticity or strength deficits on the elbow agonist muscles (such as the biceps or triceps) can drastically interfere with performance during its execution (Bohannon et al, 1991 ; Crea et al, 2017 ; Posteraro et al, 2017 ). Elbow flexion is coupled with an internal rotation and slight elevation of the shoulder.…”
Section: Methodsmentioning
confidence: 99%
“…From the kinematic variables recorded from the sensing apparatus, considering only the extension phase (all the participants had spasticity on the elbow flexors), the torque exerted at the maximum extension angle (MET) and the angle correspondent to a null exerted torque (ZTA) were extracted as indicators of the resistance to the movement. 38 The absence of mechanical or electrical failures, damages to the device, or undesired effects on the patients during the entire duration of the treatment demonstrated the safety of the device for treating patients with different body sizes and motor impairments for long periods. This behavior suggested that a treatment program provided with this device in the early post-stroke phase could contribute to the spasticity prevention.…”
Section: Clinical Studiesmentioning
confidence: 98%